SOSIALISASI PENTINGNYA MENJAGA SISTEM SALURAN DRAINASE DI LINGKUNGAN DESA LENGGAHSARI - Pratama, Ridho Pria; Danapriatna, Nana; Fakhran Al Ramadhan, Muhammad (An-Nizam, 2023)
The aim of community service activities is related to socializing the importance of maintaining the drainage system in Lenggahsari Village to increase community awareness, change community behavior to be more concerned about drainage channels, as well as active community participation in efforts to maintain and protect the drainage system and the village environment. The service method applies a socialization method targeting residents of Lenggahsari Village. The impact of the success of the program shows that residents are very enthusiastic about the socialization carried out because they gain new knowledge, residents become more concerned about the potential dangers to health and the environment if the channel is left in bad condition, and the creation of an approach program for residents who are less concerned about the environment to be more raising awareness.